Menghidupkan Identitas Kepulauan Riau Melalui Seni Tari Tradisional - Nur Sekreningsih Marsan; Mia Juliana Siregar (Gondang: Jurnal Seni dan Budaya, 2021)
This article was created with the aim of seeing the extent of the identity of Riau Islands through the art of dance known in the community and trying to revive the identity of traditional dance through documentation of the dance movement itself. Thus, the problem in this research is focused on traditional dance movements that are indeed the identity of Riau Islands identifiers, namely malay dance movements. This research was conducted by exploring the roots of the dance from art actors directly through interviews and documenting them. Through the collection of dance movement information is then documented so that it can be seen or read by all people. So that traditional dance as the identity of Riau Islands is well documented. Based on the results of the rersponden assessment, 61% stated that knowing and knowing the traditional dance of Riau Islands, the rest stated that less knowing the traditional dance. Art performances can only be enjoyed on certain occasions. To overcome this, one way to bring traditional dance identity to life is to gather information related to traditional dances and document them in the form of photos, videos and books, increasing the frequency of dance performances.